Effectiveness of a sifufbads apprentice module on sme companies in Malaysia: A case study on sifufbads apprentice student a discourse from islamic perspectives - Bahari J.; Jemain S.B.; Hehsan A.; Nazri M.K.N.Z.; Ishak M.M. (Hampstead Psychological Associates, 2024)
Indexed by Scopus/ERA